Pluralism and polyphony of voices: political participation in Hannah Arendt. Controversies of the current educational space (Praxis Educativa, 2017)
For Hannah Arendt the human duty has three fundamental activities that allow people to have a space of life in this planet, the labour: (attention to the basic needs of biological order, the labour, as work, (transformation of objects, materials: objects creation) and action (continual moment to develop the closest capacity of human being: To be free). Taking into consideration the previous information this work isanalyzed beginning from the metaphor of plurality and the polyphony of voices. The philosopher searches to give back to the subject its capacity of management its “apparition” in the polis ground. In this sense the article epitomized the theme of the educational ground
Keywords: pluralism; to dabble in politics; education and Pluralism; Hanna Arendt